Csokonai anyagi helyzetéről - Orbán, László (Studia Litteraria, 2024)
The figure of Csokonai appears to both contemporaries and posterity as a genius but impoverished poet. The only known job of the ‘poor poet’ was that of a teacher’s assistant, but he did not accept any income for his work. Several similar financial events in his life raise the question: why did he not take a regular job with a steady income, why did he give up the idea of an independent civil existence? These questions shed light on a financially difficult and seemingly contradictory life since Csokonai was able to live an independent, free, creative life in spite of all this. In line with the findings of the most recent monograph, this essay is shows that Csokonai’s career was financially supported primarily by his mother, Sara Dioszegi.